Humeanism and laws of nature: scope and limits - Soto, Cristián (Revista de Humanidades de Valparaíso, 2021)
Nomological Humeanism has developed into a research program encompassing several variations on a single theme, namely, the view that laws are statements about regularities that we find in nature. After briefly revisiting an early form of nomological Humeanism in Hume’s critique of the idea of necessary connection, this article critically examines Lewis’ two-fold approach based on Humean supervenience and the best system account. We shall point out three limits of nomological Humeanism, which are widely recognized in the literature: its inadequacy in view of physical theories, its explanatory circularity, and its purported anthropomorphism, all of which advocates of nomological Humeanism have attempted to overcome Humeanism (Jaag y Loew 2020, Loewer 2004 y Massimi 2018). Lastly, we will argue that nomological Humeanism fails to provide a suitable notion of modality for laws of nature. This latter issue continues to represent a live challenge for empiricism in the philosophy of physical laws.